The Effect of Mindfulness-Based Cognitive Therapy and Moringa Leaves on Reducing Fatigue in Breast Cancer Patients - Kundarti, Finta Isti; Titisari, Ira; Kristianto, Yohanes (Jurnal Bidan Cerdas, 2025)
Introduction: Breast cancer is the most prevalent type of cancer  among women,  with fatigue being one of  its common side effects. This study aims to ascertain the effect of Moringa oleifera and mindfulness-based cognitive therapy on fatigue in breast cancer patients. Methods: The study used a quasi-experimental design with a total of 50 respondents, divided into  an intervention group (n = 25) and a control group (n = 25), selected through simple random sampling. The study was conducted at the Bayangkara Hospital in Kediri City. The intervention group received  Moringa oleifera at a dose of 500 mg  twice daily  for 30 days  alongside mindfulness-based cognitive therapy for 8 weeks. The data were tested using a t-test  with SPPS version 17.  Results: Posttest results showed  a significant reduction in fatigue levels in the intervention group compared to the control group (m = 1.82 SD = 1.83 vs m = 3.34 SD = 2.24), p-value 0.001.  Conclusion: These findings show  a combination of Moringa oleifera and MBCT is effective in  reducing fatigue  among breast cancer patients.  The interventions are practical, non-invasive strategies that healthcare professionals can consider for improving the stamina and quality of life of breast cancer patients.